Kualitas Spermatozoa Post Thawing dari Semen Beku Sapi Perah - Zelpina, Engki; Rosadi, Bayu; Sumarsono, Teguh (Fakultas Peternakan Universitas Jambi, 2012)
The purpose of this study was to determine the effect of various thawing temperatures to the sperm quality of FH dairy cow frozen semen. The experimental design used was completely randomized design (CRD) with 5 treatments and 5 replications . The thawing treatments were 30 seconds at 33 0C (P1), 35 0C (P2), 37 0C (P3), 39 0C (P4), 41 0C (P5) . Observed variables were sperm motility, viability and recovery rate . Data were analyzed using analysis of variance . The results showed that different thawing temperatures affect the motility , viability, recovery rate of frozen spermatozoa (P<0.05). Motility and recovery rate of P4 was higher (P< 0.05) than P2 , P1 and P5 , but did not differ (P>0.05) with P3 . Viability of P4 was higher (P>0.05) than P1 and P5 but did not differ (P>0.05) with P2 and P3. In conclusion , thawing at 39 0c and 37 0C for 30 seconds had best semen quality of FH frozen semen.